The Conceptual Design of a Smart Wrist Orthosis and Functional Performance - Project Overview - Domitran, Zoran (Array, 2021)
The idea of the project was to find a conceptual design of a multi-functional smart orthosis for wrist fixation. The application of additive technologies presents the potential in designing a customised orthosis for every patient individually. By using pre-generated 3d models of various hand shapes it is possible to prepare models for several shapes and sizes of forearms and hands. The conceptual design provides a possible solution for a two-part orthosis bound around the forearm and a modular extension to stabilize the wrist without additional compression. The multi-functionality occurs with the development of a small pre-defined electronic plate located in the bottom part of the orthosis. The temperature and heart rate are constantly monitored and displayed wirelessly on a smartphone. The target group are the patients active in sports or patients with minor injuries. Moreover, the orthosis can be used for body temperature and heart function monitoring during recovery period.